Emboldening food security for global sustainability yoking artificial intelligence - Gull-e-laala Khan; Gulshan Irshad; Raina Ijaz; Sabah Javaid; Noor Tahir; Sajid Mehmood (Discover Food)
Abstract Food security is a fundamental global concern, where severe consequences may lead towards hunger and malnutrition. To intricate novel paradigm-shifting tactics correlating artificial intelligence and agriculture, the primary focus should rely on the predominant real-life implementation of AI research models addressing global food security and safety challenges. Artificial intelligence postulates noteworthy tactics improving precision agriculture models, crop-disease management, postharvest food loss reduction, smart inventory execution and global food quality assurance routes. It is estimated that future impact of AI on food safety and security will ominously increase providing better nutrition utilizing minimum agri-resources. Present study underlines AI influence in transforming sustainable future by minimizing food loss by developing a predictive and focused food security forecast following assorted socio-economic and environmental dynamics. The field of AI is practically vast and its impact on nutritional security holds central potential bridging comprehensive awareness gap for revolutionizing sustainability around the globe. From seed to fork a robust deep-learning systemic AI powered innovation models enhance global opportunities reshaping food industry and creating a resilient strategic transformation addressing food security following climate change challenges.